2016
DOI: 10.3233/npm-16915055
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of urinary tract infection in very low birth weight infants

Abstract: The incidence of UTI in contemporary VLBW infants is relatively low compared to previous decades. Since no significant UTI predictors could be identified, urine culture by sterile methods is the only reliable way to exclude UTI. The majority of infants with UTI have normal renal anatomy. UTI in VLBW infants is associated with increased morbidity and length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…Urinary tract infections are uncommon in the first 72 hours of life. Urine cultures are therefore only performed in the evaluation of LONS [35]. Lumbar puncture (LP) should be routinely performed in neonates showing signs of EONS or LONS.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…Urinary tract infections are uncommon in the first 72 hours of life. Urine cultures are therefore only performed in the evaluation of LONS [35]. Lumbar puncture (LP) should be routinely performed in neonates showing signs of EONS or LONS.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…The ability to identify patients in the neonatal intensive care unit who are at increased risk for UTI would help ensure that those patients have urine cultures [11]. In the very low-birth-weight neonates, UTI was associated with higher cholestasis, higher central line and parenteral nutrition days, prolonged mechanical ventilation, and chronic lung disease [12]. Yet, it is unclear whether these risk factors are the same for full-term neonates.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also found a low incidence of urinary tract abnormalities and VUR in a cohort of very low birth weight infants. 16 The AAP guidelines for diagnosis and management of UTI only apply to infants age 2–24 months, and do not apply to hospitalized infants in the NICU. 1 To our knowledge, there are no formal guidelines on diagnosis and management of UTI in patients admitted to the NICU, namely premature infants and infants less than 2 months of age.…”
Section: Discussionmentioning
confidence: 99%